2019
DOI: 10.1002/ajp.22950
|View full text |Cite
|
Sign up to set email alerts
|

Development of snake‐directed antipredator behavior by wild white‐faced capuchin monkeys: III. the signaling properties of alarm‐call tonality

Abstract: In many primates, the acoustic properties of alarm calls can provide information on the level of perceived predatory threat as well as influence the antipredator behavior of nearby conspecifics. The present study examined the harmonics-to-noise ratio (tonality of spectral structure) of alarm calls emitted by white-faced capuchin monkeys (Cebus capucinus) in trees directed at photographic models of a boa constrictor, neotropical rattlesnake, scorpion eater snake, and white snake-shaped control presented on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…As recent research has shown, however, some primate and avian vocal abilities are far more complex and varied than once thought (Kaplan, 2014), starting, in primates, with the discovery of referential signals in vervet monkeys, Chlorocebus pygerythrus (Seyfarth et al, 1980;Seyfarth and Cheney, 1986), continuing with the discovery of referential food grunts in chimpanzees, Pan troglodytes (Watson et al, 2015), food calls in common marmosets, Callithrix jacchus (Rogers et al, 2018), and the vocal modifications found in pygmy marmosets, Cebuella pygmaea (Snowdon, 2018). Great apes and even new world monkeys (such as black-fronted titi monkeys, Callicebus nigrifrons: Caesar and Zuberbuehler, 2012; and white-faced capuchin monkey, Cebus imitator: Coss et al, 2019) have been shown to use referential gesturing and vocalizations. Indeed, the detailed linguistically based studies of the 1980s and 1990s confirmed that apes were able to learn American Sign Language (Gardner et al, 1989;Miles, 1994).…”
Section: Backgroundmentioning
confidence: 99%
“…As recent research has shown, however, some primate and avian vocal abilities are far more complex and varied than once thought (Kaplan, 2014), starting, in primates, with the discovery of referential signals in vervet monkeys, Chlorocebus pygerythrus (Seyfarth et al, 1980;Seyfarth and Cheney, 1986), continuing with the discovery of referential food grunts in chimpanzees, Pan troglodytes (Watson et al, 2015), food calls in common marmosets, Callithrix jacchus (Rogers et al, 2018), and the vocal modifications found in pygmy marmosets, Cebuella pygmaea (Snowdon, 2018). Great apes and even new world monkeys (such as black-fronted titi monkeys, Callicebus nigrifrons: Caesar and Zuberbuehler, 2012; and white-faced capuchin monkey, Cebus imitator: Coss et al, 2019) have been shown to use referential gesturing and vocalizations. Indeed, the detailed linguistically based studies of the 1980s and 1990s confirmed that apes were able to learn American Sign Language (Gardner et al, 1989;Miles, 1994).…”
Section: Backgroundmentioning
confidence: 99%
“…The local community recognizes the existence of venomous snakes in the region, although it tends to ignore the existence of non-venomous species. This may be due to the association of the body morphology of these animals with risk factors, generally associating serpentiform animals as dangerous; given the evolutionary conditioning of human species [48], which has also been recorded in other primates [49].…”
Section: Academic Knowledgementioning
confidence: 99%
“…The local community recognizes the existence of venomous snakes in the region, although it tends to ignore the existence of non-venomous species. This may be due to the association of the body morphology of these animals with risk factors, filing in a general way the serpentiform animals as dangerous; given the evolutionary conditioning of human species [49], which has also been recorded in other primates [50].…”
Section: Discussionmentioning
confidence: 99%